I love Korean 1 - 사랑해요 한국어 1 Work Book (서울대학교출판문화원 Viện văn hóa xuất bảnTrường ĐH Seoul, 2019)
〈I Love Korean 1 Workbook〉 is the first step in the series of short-term (about 60 hours) Korean training textbooks developed by the Seoul National University Language Education Center and was developed as an supplemental textbook for practice and review of the contents learned in the main textbook.